Nucleic Acid‐Locked Smart Carrier for Photothermal/Chemotherapy‐Amplified Immunogenic Cell Death to Enhance Systemic Antitumor Efficacy - Jiayang Zhang; Tianyu Gai; Jiwei Wang; Yucai Wu; Si‐Ming Zeng; Dongyuan Zhao; Wei Li (Advanced Science)
Abstract Immunotherapy holds great promise in the fight against cancer; however, it often encounters poor immunogenicity with limited therapeutic efficacy. Combining multiple treatment modalities provides a trustworthy strategy for achieving a robust antitumor effect. In this study, a nucleic acid‐locked smart carrier (NASC) is developed to amplify immunogenic cell death (ICD) through the synergistic integration of photothermal therapy (PTT) and chemotherapy for high‐performance monotherapy. Mesoporous silica‐coated gold nanorod (MSGNR) serves as the reservoir for anticancer drug doxorubicin (DOX) and is capped with a sequence‐specific duplex unit containing a tumor‐specific targeting AS1411 fragment, resulting in the formation of NASC. With AS1411 targeting, the NASC can specifically target and be internalized into tumor cells with high expression of nucleolin, where the duplex capping can be unlocked by the intracellularly overexpressed adenosine triphosphate. Subsequently, the released DOX synergized with MSGNR‐mediated PTT following laser irradiation induces direct cell killing, which, concurrently, triggers ICD to activate antineoplastic immunity with an increased number of T lymphocytes. This triple‐collaborative strategy, further combined with anti‐programmed death‐1 antibody (αPD‐1)‐mediated immune checkpoint blockade (ICB) therapy, shows a robust therapeutic efficacy in both unilateral and bilateral tumor models.